2016
DOI: 10.1016/j.invent.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Personality predicts drop-out from therapist-guided internet-based cognitive behavioural therapy for eating disorders. Results from a randomized controlled trial

Abstract: Internet-based guided self-help cognitive behavioural therapy (ICBT) seems a promising way of delivering eating disorder treatment. However, treatment drop-out is a common problem and little is known about the correlates, especially in clinical settings. The study aimed to explore prediction of drop-out in the context of a randomized controlled trial within specialized eating disorder care in terms of eating disorder symptomatology, personality traits, comorbidity, and demographic characteristics. 109 outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…As expected, Conscientiousness positively predicted outcome from iCBT. A study on risk of dropout from iCBT for eating disorders supports this, as it found Dutifulness, a facet of Conscientiousness, to be protective of dropout (Högdahl, Levallius, Björck, Norring, & Birgegård, 2016). A concept that has been regarded as related to Conscientiousness is perfectionism, the latter an established risk-factor for developing an eating disorder (Culbert et al, 2015).…”
Section: Personality and Eating Disorder Outcomementioning
confidence: 92%
See 1 more Smart Citation
“…As expected, Conscientiousness positively predicted outcome from iCBT. A study on risk of dropout from iCBT for eating disorders supports this, as it found Dutifulness, a facet of Conscientiousness, to be protective of dropout (Högdahl, Levallius, Björck, Norring, & Birgegård, 2016). A concept that has been regarded as related to Conscientiousness is perfectionism, the latter an established risk-factor for developing an eating disorder (Culbert et al, 2015).…”
Section: Personality and Eating Disorder Outcomementioning
confidence: 92%
“…After minimal training in CBT, I was active as therapist in both treatments. Of the four therapists conducting iCBT, I had the highest dropout rate (Högdahl et al, 2016).…”
Section: Limitationsmentioning
confidence: 99%
“…A study of internet-based guided self-help found that lower scores in the personality traits of dutifulness and assertiveness and higher scores for self-affirmation best predicted drop-out 62. However, more work is needed to establish whom bibliotherapy might best target,63 especially as self-help interventions move from the traditional book to online or combined formats, some with multimedia, discussion forum and mobile components 64–66.…”
Section: Existing Empirical Evidence For Self-help and Creative Biblimentioning
confidence: 99%
“… Johansson et al, 2015 ). To date, the most common approach used in the research on IBT dropout has been based on quantitative methodologies, particularly regarding the study of predictors (e.g., Alfonsson et al, 2016 , Högdahl et al, 2016 , Karyotaki et al, 2015 , Melville et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%